2021
DOI: 10.3389/fonc.2021.614035
|View full text |Cite
|
Sign up to set email alerts
|

miR-4461 Regulates the Proliferation and Metastasis of Ovarian Cancer Cells and Cisplatin Resistance

Abstract: microRNAs (miRNAs) are of great significance in cancer treatment, which may have a desirable result on the regulation of tumorigenesis, progression, recurrence, and chemo-resistance of ovarian cancer. However, the research on the further potential application of miR-4461 in ovarian cancer is little and limited. Therefore, the study in this paper focus on the investigation of the of miR-4461 in ovarian cancer progression and chemo-resistance. The phenomenon that the proliferation and metastasis of ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…More importantly, alkannin induced apoptosis and inhibited the migration of OC cells by inhibiting the phosphorylation of Src and FAK [ 29 ], which is consistent with our results. Different from the above studies, we found that alkannin plays an antitumor effect in OC by downregulating miR-4461 [ 18 ]. Moreover, miR-4461 can promote cell growth and metastasis in OC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…More importantly, alkannin induced apoptosis and inhibited the migration of OC cells by inhibiting the phosphorylation of Src and FAK [ 29 ], which is consistent with our results. Different from the above studies, we found that alkannin plays an antitumor effect in OC by downregulating miR-4461 [ 18 ]. Moreover, miR-4461 can promote cell growth and metastasis in OC.…”
Section: Discussionmentioning
confidence: 64%
“…miR-4461 has been reported to inhibit the tumorigenesis of renal cell carcinoma by targeting PPP1R3C [ 17 ]. However, miR-4461 was regarded as a potential onco-miRNA in OC by targeting PTEN [ 18 ]. These results indicate that miR-4461 is tissue specific.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-522 has been identified to promotes ovarian cancer progression by regulating PTEN pathway [ 21 ]. miR-4461 has been revealed to promotes the proliferation and metastasis of ovarian cancer cells and cisplatin resistance via targeting PTEN [ 22 ]. miR-600 is a newly discovered miRNA, and its role and mechanism in biological development and disease are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR 4461 induces chemoresistance to cisplatin therapy in OC [ 152 ]. It augments in vitro OC cell proliferation and metastases where the knockdown of it in OC produced sensitivity to the drug via the stimulation of lipid and protein phosphatase and tensin homolog (PTEN), thereby suppressing cancer progression [ 152 ].…”
Section: Recent Advances In Cisplatin-associated Ovarian Cancermentioning
confidence: 99%
“…Cellular miR 409-3p overexpression augments sensitivity to cisplatin by conjugation of miR-409-3p and 3 0 -UTR in FIP 200 mRNA and hence, enhance FIP 200-mediated autophagy to alleviate chemoresistance in OC [151]. Furthermore, miR 4461 induces chemoresistance to cisplatin therapy in OC [152]. It augments in vitro OC cell proliferation and metastases where the knockdown of it in OC produced sensitivity to the drug via the stimulation of lipid and protein phosphatase and tensin homolog (PTEN), thereby suppressing cancer progression [152].…”
Section: Chemoresistance To Cisplatin In Ovarian Cancermentioning
confidence: 99%